Karakteristik Ensiklopedi Al-Qur’an Dawam Raharjo: Telaah Metode, Corak dan Penafsirannya - Mukhlis, Febri Hijroh; Umi Mahmudah, (QOF, 2021)
This paper elaborates on Dawam Raharjo's interpretational thoughts and works. Dawam Raharjo's research on the interpretation of the Qur'an is unique. Even Dawam offers a novel perspective on the variety of interpretations by proposing that the interpretation can be approached from a variety of scientific perspectives. Dawam offers a new perspective in the diversity of interpretations, that interpretations can be approached with various scientific backgrounds. There are two things that are the focus of this essay, namely how the character and form of Dawam Raharjo, and how the style, method and science of interpretation of Dawam Raharjo. This paper is a literary study, the focus is on the study of interpreters with a descriptive-analytical approach. The result is that Dawam Raharjo's interpretation uses the thematic method. His interpretation includes twenty-seven socio religious themes. According to him, the Qur'an has a social-societal dimension; consequently, its interpretation tends to be social based on this premise. In addition to emphasizing the social dimension of the interpretations, the themes of the interpretations also emphasize the themes of nationality and Indonesian-ness. The effort made by Dawam Raharjo to interpret the Qur'an is intriguing because the tendency of interpretation is identical to a comprehensive interpretation; Dawam provides a thematic interpretation with a real them